Transurbance: a walk about the river - Mills, Matthew (Centre for Law and Society, 2026)
This dissertation aims to address the particular social, economic and environmental issues that exist within our industrial landscape. The cities in which we live are designed to be technically enhanced but consist of functionally isolated systems that bear no relevance to the living environment. These infrastructural systems fragment our cities with linear barriers, where only functionality is measured; rivers are canalised, transport systems such as highways and railway lines separate the city from the ocean, and large industrial buildings bear no relationship to their surroundings, whilst polluting their context. The results are social and environmental disjunctions within our city. Paarden Eiland is an area that exemplifies a disconnected and disjointed environment. The particular focus of this dissertation is on a portion of the Salt River, which runs through Paarden Eiland and reaches its mouth surrounded by industrial factories. The solution that emerged consists of a long linear path that moves over and under transport barriers such as highways and railway lines, utilising the often dead residual spaces to provide a pedestrian connection to the shore. The path is continuous and unbroken but through its use of organic folds, it creates moments in which observation, interaction, play and discovery can take place. This constructed path forms a weir in the river, bringing floating debris to a recycling centre, where it can be re-purposed into usable components that restore the river. Through a close reading of existing site conditions, the architecture attempts to merge landscape, building and infrastructure into one, in order to create a new architecture that is intricately connected to its site and its users. This architecture plays with the definitions of the man-made and the natural, creating a design that can rehabilitate the environment, and illustrate the destruction man has wrought on nature. It is my belief that the design will be able to shift its users' understanding of the environment, to one where technology and nature can exist not only harmoniously but also symbiotically.